Experimental and modelling studies of low temperature PEMFC performance. (18th March 2020) - Chugh, Sachin; Chaudhari, Chinmay; Sonkar, Kapil; Sharma, Alok; Kapur, G.S.; Ramakumar, S.S.V.
Abstract: The performance of a PEMFC (Polymer Electrolyte Membrane Fuel Cell) is greatly influenced by the various operating variables like temperature, pressure, stoichiometry of reactants and humidity. The presented work deals with the experimental study of 30 cells low temperature PEM fuel cell stack employing Nafion®-212 membranes. Experimental results are discussed with polarization curves and compared with the steady state model results, developed in MATLAB. The model predicts increase PEMFC performance with increase in operating temperature, pressure and reactant humidity. The comparison shows good agreement between experimental and modeling results with deviations in the range of 7–15% only. Highlights: · Experimental evaluation of operating parameters' effect on fuel cell performance. · Steady state mathematical model development in MATLAB . · Model validation by comparison with experimental results. · Identification of optimum operating parameters.